Effect of Donor Age and Corneal Endothelial Cell Density on Non-utilization of Donor Corneal Tissues: A Study From Indian Eye Banks. Issue 6 (27th June 2022) - Roy, Aravind; Chaurasia, Sunita; Fernandes, Merle; Mohamed, Ashik; Murthy, Somasheila; Das, Sujata
Abstract : Purpose: To study the causes of non-utilization of donor corneas and assess whether non-utilized tissues differ from utilized tissues with regard to age and endothelial cell density (ECD). Methods: Aretrospective, cross-sectional analyses of all donor corneas collected from a network of 4 eye banks of a tertiary eye care institute in India during a 1-year period (January to December 2019) was conducted. All donor corneas were assessed for tissue quality by slit lamp evaluation, donor age, and specular microscopy. The causes of non-utilization and effect of donor age and ECD on tissue utilization were studied. Results: A total of 10, 969 corneas were harvested during the study period; 4618 (42.1%) tissues were discarded. The main causes of non-utilization were poor tissue quality accounting for 86.16% (n = 3979) of all discarded corneas. The mean donor age was 50.7 ± 2.9 years and 63.3 ± 2.3 years for used and discarded corneas, respectively ( P < 0.0001). The mean ECD of donor tissues was significantly ( P < 0.0001) higher in the utilization group (2787.3 ± 77.4 cells/mm 2 ) than that in the non-utilization group (2394.4 ± 82.5 cells/mm 2 ). Donor age and ECD and their interaction were significant ( P < 0.001) predictors of tissue utilization rate. Conclusions: Donor age and ECD and their interaction were significantly associated with the rate of utilization of donor corneal tissues.